2021
DOI: 10.3389/fmicb.2021.642587
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Chemical Fertilizer Application to Wheat Reduces the Abundance of Putative Plant Growth-Promoting Rhizobacteria

Abstract: The profound negative effect of inorganic chemical fertilizer application on rhizobacterial diversity has been well documented using 16S rRNA gene amplicon sequencing and predictive metagenomics. We aimed to measure the function and relative abundance of readily culturable putative plant growth-promoting rhizobacterial (PGPR) isolates from wheat root soil samples under contrasting inorganic fertilization regimes. We hypothesized that putative PGPR abundance will be reduced in fertilized relative to unfertilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 69 publications
2
27
0
Order By: Relevance
“…Interestingly, in the roots from organic farms, we found an increased abundance of Bradyrhizobium, Streptomyces, Burkholderia-Caballeronia-Paraburkholderia, and Sphingomonas, all of which are genera enriched by well-known plant growth-promoting bacteria [47][48][49][50]. This result is consistent with a recent report by Reid et al [43] showing a reduction in the population of plant growth-promoting bacteria in the rhizosphere after applying chemical fertilizers. Through both previous studies and this present study, we can see the benefit of organic cropping systems on microbial composition, which might increase crop growth and resilience to environmental stresses.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, in the roots from organic farms, we found an increased abundance of Bradyrhizobium, Streptomyces, Burkholderia-Caballeronia-Paraburkholderia, and Sphingomonas, all of which are genera enriched by well-known plant growth-promoting bacteria [47][48][49][50]. This result is consistent with a recent report by Reid et al [43] showing a reduction in the population of plant growth-promoting bacteria in the rhizosphere after applying chemical fertilizers. Through both previous studies and this present study, we can see the benefit of organic cropping systems on microbial composition, which might increase crop growth and resilience to environmental stresses.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies showed that Acidothermus and Rhodanobacter preferred saline and acidic environments, respectively [35,41]. It is known that the long-term application of chemical fertilizers affects soil pH and salt content, and has a great impact on microbial community composition in the rhizosphere [42,43]. Further studies will be required to examine the seasonal change in soil fertility, plant nutrition status and microbiome to reveal the association between microbiomes and other environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of chemical fertilizers has a negative impact on the soil microbiome, as plants no longer need to interact with beneficial bacteria to access the nutrients that are being externally supplied and, therefore, the diversity of the microbial community in the root environment is reduced ( Zhu et al, 2016 ; Kavamura et al, 2018 ). A study performed in wheat has shown that chemical fertilizers reduce the number of bacteria associated with the roots that solubilise nutrients such as nitrogen, potassium, phosphorous, iron, and zinc ( Reid et al, 2021 ). Strikingly, the number of growth-promoting bacteria living on the roots fell from 91% of total bacteria for unfertilized plants, to just 19% for those that received the fertilizer dose.…”
Section: Moving Toward Tailored Inoculantsmentioning
confidence: 99%
“…SoapAligner software 2.MetaGeneMark software 3. CD-HIT software 4.BLAST software When the rhizosphere and detrituspheric microbiomes collaborate in the presence of decaying roots, it is observed that the rhizospheric microbiome degrades the plant root exudates, and the specific genes corresponding to membrane transporters, amino acid, and carbohydrate metabolism enhance their expression 5 [ 110 ] Wheat To study the response of chemical fertilizers on putative PGPR richness present in the commercial Cadenza, the wheat variety is grown in a low input agricultural soil exhausted in most nutrients. Under such conditions, the beneficial microbes are known to have a key role in sustaining the crop growth and production CASAVA data analysis software (Illumina) The rhizobacteria present in the soil is beneficial to plants as it is involved in insoluble nutrients mobilization in soil but in the presence of chemical fertilizers, its population is decreased considerably 6 [ 111 ] Wheat To study the collective response of eCO2 and nitrate levels on the function and structure of the bacterial community attached to the root surface 1.StepOne software v2.3 (Applied Biosystems) 2.CD-HIT-EST v4.8.1 3.MEGAN v6.15.2 4.Trinity mapping v2.8.4 5.Cytoscape v.3.7.2 The combined effect of CO2 and nitrate levels are responsible for plant growth and development and is also benefit the growth and function of the root surfaceassociated bacterial population which is involved in the fitness of root and root colonization 7 [ 112 ] Chickpea To analyze endophytic bacterial communities for their functionality and diversity present in internal root tissues of native legumes species growing into different locations of south Portugal further assess its potential to accelerate plant development and growth Tree of Life (iTOL) v4 The association of rhizobia and specific non –rhizobial endophytic bacteria elevates the growth of chickpea majorly via increasing the nodulation and nitrogen fixation capacity shown by mesorhizobial strains 8 [ 113 ] Sorghum To determine the time dependent change in the microbial complexity in the rhizospheres of field-grown sorghum USEARCH software suite An OUT of bacterial origin from the genus Pseudomonas was identified in the microbiome of the rhizosphere of Sorghum bicolor.…”
Section: Introductionmentioning
confidence: 99%